2009
DOI: 10.1002/jez.530
|View full text |Cite
|
Sign up to set email alerts
|

A cineradiographic study of lung ventilation in Alligator mississippiensis

Abstract: The skeletal and visceral kinematics of lung ventilation of the American alligator (Alligator mississippiensis) was examined using cineradiography, pneumotachometry, and intrapulmonary pressure recording. The respiratory pattern of A. mississippiensis is intermittent and diphasic. The inspiratory lung volume is retained during the non-ventilatory period through closure of the glottis. The aspiration pump of A. mississippiensis consists of multiple components: visceral movement, pubic rotation, gastralial movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(99 citation statements)
references
References 46 publications
3
96
0
Order By: Relevance
“…These studies suggest that the diaphragmaticus muscle plays a primary role in inspiration. This argument is further supported by recent videoradiographic measurements of lung volume in resting alligators (Claessens, 2009), where the diaphragmatic contribution to lung inflation has been determined to range from 36% to 61% of inspired tidal volume.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…These studies suggest that the diaphragmaticus muscle plays a primary role in inspiration. This argument is further supported by recent videoradiographic measurements of lung volume in resting alligators (Claessens, 2009), where the diaphragmatic contribution to lung inflation has been determined to range from 36% to 61% of inspired tidal volume.…”
Section: Introductionmentioning
confidence: 66%
“…Relatively large (up to 7.5kg) submerged caimans were used in studies that reported low EMG activity of the intercostals and a high reliance on the diaphragmaticus muscle for inspiration (Gans, 1971;Gans and Clark, 1976). Videoradiographic studies in juvenile alligators (mass 0.72-2.09kg) estimated that 36-61% of V T was attributable to diaphragmaticus activity and ~40% attributable to costosternal activity (Claessens, 2009), although it should be noted that these estimates were calculated for V T values 2-4-fold larger than those measured at rest in this study. While the diaphragmaticus muscle is well developed in adults, it is thin and translucent in juvenile crocodilians (S.L.M., personal observations).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvic aspiration and hepatic piston action are part of normal crocodilian breathing cycles (141). However, their involvement in buoyancy control suggests origination in an ancient aquatic crocodiliomorph lineage, that is, not a shared trait with archosaurs (759).…”
Section: Section 3 Air Breathing In Vertebrates: Transition From Watmentioning
confidence: 99%